Role of magnetoelastic coupling and magnetic anisotropy in MnTiO3 - Gries, Lukas; Jonák, Martin; Elghandour, Ahmed; Dey, Kaustav; Klingeler, Rüdiger (Physical review, 2022)
We report the thermodynamic properties studied by thermal expansion, magnetostriction, magnetization, and specific heat measurements as well as the low-energy magnetic excitations of MnTiO3 and investigate how magnetoelastic coupling and magnetic anisotropy affect the evolution of long-range order and the magnetic phase diagram. Specifically, we utilize high-resolution capacitance dilatometry and antiferromagnetic resonance (AFMR) studies by means of high-frequency electron spin resonance (HF-ESR) spectroscopy. The role of anisotropy is reflected by spin reorientation at BSF≃6T and a corresponding sign change in ∂TN/∂B. Analysis of the AFMR modes enables us to establish the zero-field excitation gap Δ as well as its temperature dependence. We derive the effective anisotropy field BA=0.16(1)T which predominately originates from out-of-plane nearest-neighbor magnetic dipole interactions. Despite the nearly fully quenched orbital moment, our data show pronounced thermal expansion and magnetostriction anomalies at TN and BSF, respectively, which allows the experimental determination of sizable uniaxial pressure dependencies, i.e., ∂BSF/∂pc=−0.20(2)T/GPa, ∂TN/∂pb=0.69(12)K/GPa, and ∂TN/∂pc=−2.0(4)K/GPa. While in the thermodynamic properties the presence of short-range magnetic order up to ≃170K is detected by anisotropic lattice distortion and by the violation of a constant Grüneisen behavior, the presence of local magnetic fields is seen in ESR at even higher temperatures of at least 3TN.
Im Titel ist die Zahl 3 tiefgestellt
Gesehen am 27.01.2023